A Preliminary Study Of Risk Factors Of Breast Cancer And The Usefulness Of Breast MRI As An Addition To Mammography In Detecting Breast Cancer In High Risk Women - Hashim, Nur Hashamimi (2016)
The risk factors of breast cancer among women, such as genetic, family history and lifestyle factors, can be divided into high, intermediate and average-risk. Screening of breast cancer which include mammography, can be done in promoting early breast cancer detection. Breast magnetic resonance imaging (MRI) has been recommended as a supplemental screening tool in high risk women. Therefore, the aim of this study was to identify the significant risk factor(s) of breast cancer among women and also to determine the usefulness of breast MRI as an addition to mammography in detection of breast cancer in high risk women.